A STUDY OF TURN TAKING IN EXTENSIVE READING LECTURE AT ENGLISH STUDY PROGRAM OF HALU OLEO UNIVERSITY - Anwair, Suhartono (Journal of Teaching of English, 2019)
The study of turn taking in extensive reading lecture is aimed at investigation the types of turn taking and its functions. The scope of this study is restricted only to the classroom interaction in extensive reading lecture. There are 30 students and 1 lecturer taken as the respondents. They are taken by purposive sampling. In collecting the data, all utterances produced by the speakers were recorded and scripted. Finally, those scripts were analyzed by using descriptive qualitative method in terms of types of turn taking and its functions.The result shows that there are three turn taking types in extensive reading lecture, namely: taking the turn, holding the turn and yielding the turn. Additionally, there are eleven functions of turn taking in extensive reading lecture, namely: informative, organisation, affective, responsive, external thinking, interrogative, judgemental, intentional, hypothetical, reproductional, and imaginative functions.Â Keywords: turn, turn taking, and extensive reading lecture